2021
DOI: 10.21608/besps.2021.66777.1097
|View full text |Cite
|
Sign up to set email alerts
|

Study the Effect of Silymarin on Cyclophosphamide Induced Testicular Damage in Adult Albino Rats

Abstract: Background: cyclophosphamide one of toxicants that induce testicular damage. Silymarin has antioxidant and antiapoptotic properties. Aim: assess the effect of silymarin on cyclophosphamide induced testicular damage in male albino rats. Materials and Methods: This study was conducted on 40 adult albino male rats that were divided into 4 groups. control group: were injected intraperitoneally with carboxy-methylcellulose daily for six weeks. Cyclophosphamide group: were injected intra-peritoneally with cyclophosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In the present study, silymarin was used as an antioxidant, and we found that rats exposed to CP plus silymarin had higher levels of antioxidative markers such as GSH, SOD, and CAT and lower levels of MDA (free radicals' markers). Similar results to our study were recorded in rats' liver, kidney, and testis exposed to CP plus silymarin compared to CP only (10,11,24). In this study, the antioxidant property of silymarin exposure plus CP led to ameliorating the structural pathological changes that appeared due to only CP exposure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, silymarin was used as an antioxidant, and we found that rats exposed to CP plus silymarin had higher levels of antioxidative markers such as GSH, SOD, and CAT and lower levels of MDA (free radicals' markers). Similar results to our study were recorded in rats' liver, kidney, and testis exposed to CP plus silymarin compared to CP only (10,11,24). In this study, the antioxidant property of silymarin exposure plus CP led to ameliorating the structural pathological changes that appeared due to only CP exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Silymarin is one of the most potent hepatoprotective chemicals, a natural flavonoid produced from Milk thistle or Silybum marianum (a member of the Asteraceae family) (8). Silymarin has antiinflammatory, anti-cancer, and antioxidant effects by scavenging free radicals and raising glutathione peroxidase levels (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, FSH and LH play a role in regulating Leydig cell function to produce testosterone in males [ 8 ]. CP markedly reduced the serum levels of testosterone, FSH, LH, and prolactin [ 11 ], even at a single dose of 100 mg/kg [ 34 ]. The results of this study indicated that CP affected spermatogenesis by interfering with cellular processes as well as the pituitary–testicular axis.…”
Section: Discussionmentioning
confidence: 99%